Management Of Haemorrhagic Ovarian Cyst By Ayurveda Regimen: A Case Report - Jha, Khushboo; Choudhary, Poonam; Bharathi, K; Sonu (International Research Journal of Ayurveda & Yoga, 2024)
The granulosa layer of the ovary remains avascular until the time of ovulation. After ovulation occurs, the granulosa layer quickly becomes vascularized by thin-walled vessels, which rupture easily, giving rise to a hemorrhagic cyst. The disease Granthi (Cyst), simulating the description of Cyst (the disease arising due to excessive, uncommon or peculiar and improper growth of cells) has been mentioned in Ayurveda, but it can be called as Beejakosha Granthi. Charaka has indicated enucleation of Granthi (Cyst) along with its kosa or capsule in the treatment, on this basis some of the workers have equated Granthis with cysts. A 20 yrs. female visited OPD of NIA PTSR with chief complaint of pain in lower abdomen for 5 years on 15 July 2020. Her abdominal pain was also associated with anorexia, wt. loss and breathlessness. She had also brought her sonography report and some other blood investigations along with her. She was diagnosed as Right hemorrhagic cyst (52x53mm). Then patient was advised for oral medications as Kanchanar kashya, Avipatikar churna, Pittantak, Muktashukti, Sanjeevani vati, Sitopaladi churna, Godanti bhasma, Punarnava mandoor. The patients took the medications for six months. After she went through sonography which revealed normal.